Impact of International Trade Regimes on mineral beneficiation in developing countries: the case of fluorspar in South Africa - Motsie, Phokojoe Refiloe (My University, 2021)
Developing countries have long been relegated to the role of raw material suppliers. In order to diversify their economies, developing countries must transition their economies from being dependent on mineral extraction, to high-value add industries. The problem with the reliance solely on extraction sectors is that their economies are heavily exposed to market externalities such as demand and price fluctuations of commodities. Economic diversification is therefore key in advancing the developmental agenda of any country. The current structure of international trade regimes indirectly perpetuates the dependence of developing countries on supplying raw materials to developed countries then later import them as processed and finished goods. This phenomenon has led to low or lack of investment in value addition linkages in many developing countries. To further exacerbate the situation, import tariffs on processed products are generally higher than on raw materials, showing some tariff escalation disparity. This report investigated the impact of tariff escalation on processed goods as one of the main factors that impede local beneficiation in developing countries. The report also considered the contrasting views that in as much as there is a strong drive for developing countries to beneficiate their raw minerals, few have internal markets large enough to make them economically viable. In a bid to address the issue of turning comparative advantage to competitive advantage by considering tariff regime structures, the report looked at the value proposition that can be derived from the South African fluorspar industry as a case study by using the partial equilibrium modelling tool (SMART) from the World Bank. The SMART modelling tool was used because it allows for analysis of data at a disaggregated level and carters for comparison between different trade databases. From the results it was established that South Africa could stimulate downstream beneficiation activities in the fluorspar value chain by using the hybrid tariff structure to support the establishment of a fluorchemical industry
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters in Engineering, 2021